2018
DOI: 10.1016/j.rbmo.2018.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Ulipristal acetate for the management of large uterine fibroids associated with heavy bleeding: a review

Abstract: Ulipristal acetate (UPA), a selective progesterone receptor modulator (SPRM), offers new therapeutic options for the clinical management of large uterine fibroids associated with heavy menstrual bleeding or with other moderate or severe symptoms (bulk symptoms, pelvic pain, decreased quality of life). SPRM are synthetic compounds that exert an agonist or antagonist effect on target tissues by their binding to progesterone receptors. UPA reduces fibroid size, controls bleeding in a high percentage of women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 42 publications
(102 reference statements)
0
21
0
1
Order By: Relevance
“…The appropriateness of employing an antiprogestin-activated transactivator in a RCCV-based vaccine may need to be re-evaluated in light of more recent developments. Pivotal clinical trials demonstrated that ulipristal is capable of reducing the size of uterine fibroids, resulting in marketing approvals of the ulipristal-containing drug Esmya (Gedeon Richter Plc, Budapest, Hungary) in Europe and Canada [43][44][45]. A typical treatment involves one or more treatment cycles of up to three months (5 mg/day of ulipristal taken orally).…”
Section: Additional Thoughts On the Antiprogestin Co-control Of Rccvsmentioning
confidence: 99%
“…The appropriateness of employing an antiprogestin-activated transactivator in a RCCV-based vaccine may need to be re-evaluated in light of more recent developments. Pivotal clinical trials demonstrated that ulipristal is capable of reducing the size of uterine fibroids, resulting in marketing approvals of the ulipristal-containing drug Esmya (Gedeon Richter Plc, Budapest, Hungary) in Europe and Canada [43][44][45]. A typical treatment involves one or more treatment cycles of up to three months (5 mg/day of ulipristal taken orally).…”
Section: Additional Thoughts On the Antiprogestin Co-control Of Rccvsmentioning
confidence: 99%
“…Hormonal medical treatment for uterine fibroids include combined oral contraceptives, levonorgestrel intrauterine device (LNG-IUD), progestins, gonadotropinreleasing hormone (GnRH) agonists, androgenic steroids, and selective progesterone receptor modulators (SPRMs) (Donnez et al 2018;Esmya 2012;Laughlin-Tommaso 2016;Lumsden et al 2015;Singh et al 2018;Vilos et al 2015).…”
Section: Medical Treatmentmentioning
confidence: 99%
“…Отмечено, что у некоторых пациенток, получавших терапевтическую дозу УПА, могут наблюдаться признаки идиосинкразического ЛПП с потенциально серьезными клиническими последствиями в связи с повышенной чувствительностью к препарату. К сожалению, в настоящее время не известны биомаркеры, которые можно было бы использовать для выявления таких пациенток до начала лечения [32,33].…”
Section: селективные модуляторы прогестероновых рецепторовunclassified